Multi-objective optimization and decision visualization of batch stirred tank reactor based on spherical catalyst particles - Antanas Žilinskas; Romas Baronas; Linas Litvinas; Linas Petkevičius (Nonlinear Analysis, 2019)
This paper presents a Bayesian approach rooted algorithm oriented to the properties of multi-objective optimization problems. The performance of the developed algorithm is compared with several other multi-objective optimization algorithms. The approach is applied to the multiobjective optimization of a batch stirred tank reactor based on spherical catalyst microreactors. The microbioreactors are computationally modeled by a two-compartment model based on reaction–diffusion equations containing a nonlinear term related to the Michaelis–Menten enzyme kinetics. A two-stage visualization procedure based on the multi-dimensional scaling is proposed and applied for the visualization of trade-off solutions and for the selection of favorable configurations of the bioreactor.